Pengaruh Harga Tiket dan Pelayanan Terhadap Keputusan dalam Menggunakan Kapal Penumpang pada PT. Pelayaran Nasional Indonesia (Persero) Cabang Surabaya - Latue, Shilsilia; Akhmad, Ekka Pujo Ariesanto (Universitas Hang Tuah, 2022)
The Indonesian sea transportation industry is a growing industry, getting smarter, price conscious, and competitive. This competitive competition is experienced not only with domestic sea transportation but also with international sea transportation. This study examines the effect of ticket prices and services on the decision to use passenger ships at PT. Pelayaran Nasional Indonesia Surabaya branch, the object of this research is PT. Pelni Surabaya Branch. The research population is all passengers on the Pelni ship. The number of samples drawn using the iteration formula is 116 people and this study uses quantitative methods and multiple linear regression analysis techniques. The results of the study stated that the ticket price partially had a positive and significant effect on the decision to use the passenger ship PT. Pelni. This can be proven by the results of tcount of 10.795 > from ttable = 1.981 with a significance level of 0.000 <0.05, the service partially has a positive and significant effect on the decision to use the passenger ship PT. Pelni. This can be proven by the results of tcount of 2,323 which is greater than ttable = 1,981 with a significance level of 0.022 < 0.05 that prices and services have a positive and significant effect on the decision to use the passenger ship PT. Pelni. This is evidenced by the significant value of F count 102,917 which is greater than F table of 3.08 and the significance level of 0.000 is less than 0.05.